The effect of compound exercises (physical - skill) in the development of some physical abilities and basic skills football - Baraa , Deaa Al-Deen (Journal of Physical Education, 2012)
The research problem is the following:One researcher there is a weakness in physical abilities and some other basic skills which will affect the effectiveness of their performance, the majority of the Iraqi divisions suffer from the apparent decrease in the level of performance, particularly in the last third of the game as it leads to fatigue early and slow the case of hospitalization, and to the lack of focus and the low level of effectiveness of the overall performance (physical and technical) that shows through play and indiscriminate dispersal of the balls and the large number of Almanaullac broken and slow events defensive and offensive, and not to focus on the application of scientific methods, to reach the perfect performance and the result is positive in football, as it is physical abilities essential foundation upon which the development of the physiological and skill and tactical and psychological.The research aims to:1.Vehicle preparation exercises (physical - skill) to develop some physical abilities and basic skills for football.2.Identify the impact of exercise on the vehicle (physical - skills) in the development of some physical abilities and basic skills of football players (under research).The researcher assumed the following:1.There are significant differences between the moral tests of tribal and dimensional capabilities of the physical and basic skills and for post-test.And the research community to ensure that football players from the youth enrolled in the Iraqi Central Football Season 2010-2011 and the participants in the Youth League, while the sample 12 for the player of the football team for young students.The researcher suggested the following:.1.the compound exercises that I use a researcher had a positive impact in the development of physical abilities and skills under study for the young football players, 0 and as follows:2.led exercise vehicle that I use a researcher to the positive impact of the development of physical abilities of football (with strength, with speed, and power deals as soon as a man right, a man who left), as the biggest moral value emerged among members of the research sample in the physical tests, she was in the capacity of ( with speed and force with force and speed of a man who deals right, left, a man) and this is consistent with the needs of soccer players in this capacity during the game.3.that exercise resulted in the vehicle that I use a researcher to have a positive impact of the development of some basic football skills (handling, scoring, and Ro).4.exercise the vehicle led to the evolution of man's right by more than the man left in the tests as soon as the force deals.The researcher recommends the following:1.exercises confirm the use of the vehicle and give it great importance in the course of training modules in preparation for private and competitions for various age groups for youth and junior football, because they lead to the development of physical abilities and skills.2.focus on the development of physical abilities, especially the speed of the bearing speed using exercises with short-haul, medium and determine Tkaradtha and timing, and taking into account the rest period and nature of accurate and practical to re-healing and in proportion to the need of a football player and allows the player to re-implement exercises competence, because it represents the fundamental basis from which the player to implement the technical and tactical aspects.3.attention to building basic skills in accordance with valid scientific basis, which provides the time and effort and improved performance to better the future.